Urbanisme civique en temps de crise : les espaces publics d'Hispanie et de l'Occident romain entre les IIe et IVe s. - Brassous, Laurent; Quevedo, Alejandro (Collection de la Casa de Velázquez, 2015)
Articles dealing with the history of cities in the Western Roman Empire from the height of the empire to late antiquity.